Giant placental chorangioma: The first case report in Indonesia - Emilia Theresia; Detty Siti Nurdiati; Irianiwati Widodo (Elsevier, 2021)
Giant placental chorangioma is a benign non-trophoblastic neoplasm which is rare but often results in serious prenatal complications and adverse pregnancy outcome. Here, we present the first case report of giant placental chorangioma in Indonesia with good clinical outcome, prenatally detected in a 35-year-old G4P2A1 female patient, who presented at 33 weeks of gestation with placenta previa, hemorrhage, anemia, and cardiomegaly. The color Doppler ultrasonography examination showed a large cystic hypoechoic circumscribed intraplacental mass in the parenchymal placenta. The elected caesarian section and mass removal was performed at 36 weeks of gestation. The microscopic appearance of the tumor showed a proliferation of capillary sized vessels with monomorphic endothelial cells. The tumor cells showed immunoreactivity for CD31, CD34, and smooth muscle actin (SMA). The Ki-67labeling index was 30%. Clinical, radiological, histopathological, and immunohistochemical profiles confirmed the diagnosis of giant placental chorangioma.